2017
DOI: 10.1111/jfd.12679
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pathogenicity of Vibrio spp., Photobacterium damselae ssp. damselae and five isolates of Aeromonas salmonicida ssp. achromogenes in juvenile Atlantic halibut (Hippoglossus hippoglossus)

Abstract: Juvenile Atlantic halibut (~100 mg, Hippoglossus hippoglossus) were exposed to Vibrio proteolyticus, a Vibrio spp. isolate, Photobacterium damselae ssp. damselae and five different isolates of Aeromonas salmonicida ssp. achromogenes via an hour‐long bath immersion to ascertain their variation in pathogenicity to this fish species. Results were analysed using Kaplan–Meier survival analysis. Analysis of the data from challenges using A. salmonicida ssp. achromogenes revealed three survival values of zero and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“… Vibrio proteolyticus ( Vpr ) is a Gram-negative marine bacterium. Vpr strains were isolated from diseased corals ( 3 ) and were shown to be virulent to fish ( 4 ) and crustaceans ( 5 ). We previously reported that Vpr strain NBRC 13287 (ATCC 15338) has 3 anti-eukaryotic determinants: a secreted pore-forming hemolysin (VPRH) that kills mammalian cells, and 2 type VI secretion systems (T6SS1 and T6SS3) that deliver anti-eukaryotic effector proteins into mammalian phagocytic cells ( 6 8 ).…”
Section: Observationmentioning
confidence: 99%
“… Vibrio proteolyticus ( Vpr ) is a Gram-negative marine bacterium. Vpr strains were isolated from diseased corals ( 3 ) and were shown to be virulent to fish ( 4 ) and crustaceans ( 5 ). We previously reported that Vpr strain NBRC 13287 (ATCC 15338) has 3 anti-eukaryotic determinants: a secreted pore-forming hemolysin (VPRH) that kills mammalian cells, and 2 type VI secretion systems (T6SS1 and T6SS3) that deliver anti-eukaryotic effector proteins into mammalian phagocytic cells ( 6 8 ).…”
Section: Observationmentioning
confidence: 99%
“…In addition, despite being the most reliable method, the challenge method by intraperitoneal injection is not the natural route of infection and thus might affect the results (Bowden et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 12, 2022. ; https://doi.org/10. 1101/2022 Vibrio proteolyticus (V. proteolyticus) is a Gram-negative marine bacterium that was isolated from diseased corals (Cervino et al, 2008); it was also shown to cause mortality in fish (Bowden et al, 2018) and in the crustacean model organism, Artemia (Verschuere et al, 2000). V. proteolyticus does not possess a type III secretion system (T3SS) that can mediate delivery of effector proteins directly into host cells (Miller et al, 2019;Ray et al, 2016).…”
Section: Introductionmentioning
confidence: 99%